KORELASI GEOKIMIA MOLEKULER MINYAK BUMI PETAPAHAN-KAMPAR DENGAN SUMUR MINYAK BUMI LANGGAK, PENDALIAN ROKAN HULU, RIAU - Rita Marlina; Emrizal Mahidin Tamboesai; Amir Awaluddin (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
To date, crude oil  has been  the main energy resources  for  industry, transportation and household needs. The demand for crude oil in Indonesia is much higher than its production which leads to current energy crisis. One of solutions for this crisis is to conduct correlation study, which determines the genetic relationship at each oil well. The correlation study of crude oil  in Petapahan Kampar with Langgak and Pendalian Rokan Hulu has not been conducted previously. This study could assist to provide the indication of the genetic relationship, deposition zone, souce rock and the origins of Petapahan, Langgak and Pendalian’s crude oil. The crude oil samples taken  from oil wells was firstimmediately refrigerated before conducting geochemistry analysis. The samples were then fractionated by column to separate saturated fraction. This fraction was analyzed using Gas Chromatography (GC). On the basis of the abudance of hydrocarbon aliphatic, the crude oils samples  have small ratio value, which  are  0,44-0,55 for Pr/n-C17 and 0,20-0,26 Ph/n-C18. This values indicated that the samples were originated from higher vascular plants (terrestrial). The samples derived from lacustrine environments (lake) have ratio value of Pr/Ph (2,14-2,39). The calculation from Star diagram have showed that the samples of production oil field in Petapahan 19, Petapahan  23, Langgak 016  are positively correlated , whereas the oil samples in area 03  are negatively correlated. The positive correlation indicated that the samples have the genetic relationship at each oil, a same  source matter, and same the original.